Regulation peculiarities of cooperative banking in Poland - Kania, Ewa; Łękawa, Zofia (Ekonomika, 2009)
The dual nature of cooperative banks is reflected by their formal and institutional solutions. They refer both to banking and to cooperative regulations, especially to those dedicated to relations between the two areas; hence, they result from considering their specialness and consistency. In addition to general cooperative principles which define membership rules in the first place, this paper focuses on codes ruling the coexistence of cooperative banks within a given domain and organizational solution. They include: – collaboration of cooperative banks within a federated structure as forms of association between cooperative (member) banks and the associating bank; – regionalization which defines the framework of coexistence and is combined with the territoriality of operations, or the right to operate in a limited area as independent units with no competition among respective cooperative banks; – subsidiarity which is tightly related to the division of functions between a primary level (cooperative banks) and a higher level (associating banks). This paper aims at identifying to what extent the regulations should be dedicated to cooperative banks or what real impact of cooperative specialness is on legal is solutions. Thus, a diligent examination is necessary to identify those elements of cooperative banking which require dedicated solutions and those which are identical with commercial banking. The solutions are significantly diversified, although there have been attempts to standardize them in some areas following the need to comply with the European standards and regulations, including recommendations issued by the National Union of Cooperative Banks and the European Associations of Cooperative Banks in the EU.